2022
DOI: 10.3389/fpsyg.2022.934029
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the distribution of attention to trained procedure between finders and non-finders of the alternative better procedure

Abstract: The human ability to flexibly discover alternatives without fixating on a known solution supports a variety of human creative activities. Previous research has shown that people who discover an alternative procedure relax their attentional bias to information regarding the known solutions just prior to the discovery. This study examined whether the difference in the distribution of attention between the finders and non-finders of the alternative procedure is observed from the phase of solving the problem using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For instance, think-aloud protocols in Blech et al (2020) show that participants keep starting with the wrong element. Recent eyetracking work suggests that attention remains allocated to elements involved in the standard solution in those participants who do not eventually shift to the alternative strategy ( Ninomiya et al, 2022 ). In a similar vein, eyetracking in chess problems has shown that a known solution captures attention even though problem solvers believe that they are occupied with an alternative solution approach ( Bilaliæ et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, think-aloud protocols in Blech et al (2020) show that participants keep starting with the wrong element. Recent eyetracking work suggests that attention remains allocated to elements involved in the standard solution in those participants who do not eventually shift to the alternative strategy ( Ninomiya et al, 2022 ). In a similar vein, eyetracking in chess problems has shown that a known solution captures attention even though problem solvers believe that they are occupied with an alternative solution approach ( Bilaliæ et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…While with water jar problems (cf. Luchins and Luchins, 1994 ; Blech et al, 2020 ; Ninomiya et al, 2022 ) or chess problems (cf. Bilaliæ et al, 2008 ; Sheridan and Reingold, 2013 ) participants need to be selected such that their skills are sufficient to perform the basic tasks (mental calculation or playing chess at a decent level), our covariation learning task is more broadly applicable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation